European Society of Surgical Oncology Young Surgeons (Young ESSO): a path for training excellence, inclusive leadership and research engagement - Caballero, Carmela; Brandl, Andreas; Santrac, Nada; Vasileva-Slaveva, Mariela; Bonci, Eduard-Alexandru; Sochorova, Dana; Kaul, Pallvi; Vassos, Nikolaos; Lecoq, Carine; Lorenzon, Laura; Polom, Karol (European journal of surgical oncology, 2025)
Young ESSO, previously called ESSO Young Surgeons Alumni Club (EYSAC), is a committee facilitating meaningful collaborations for cancer surgery training and research among ESSO's young members. It is composed of ESSO members ≤45 years old and led by a Steering Committee and National Representatives from >50 countries. Young ESSO has evolved into a well-structured, influential community within ESSO. It contributes to the ESSO Research Academy and to the Educational Training Committee. We describe its history, structure and contribution to the mission and vision of ESSO: to cure cancer together through multidisciplinary approach, precision surgery and harmonized high-quality training in cancer surgery. As a pathway for leadership and research engagement for early-career surgeons, it represents ESSO's commitment to education and career development. We aim convey the aspirations Young ESSO for inclusiveness, advocating for women as leaders in surgical oncology and addressing disparities in cancer surgery training within and beyond Europe.
Online verfügbar: 14. Juli 2025, Artikelversion: 22. Juli 2025
Gesehen am 21.08.2025